The effect of body incidence on the forces and moments on two afterbodies with a rearward facing jet in a subsonic uniform flow - Craven, A.H. (College of Aeronautics, 1958)
This paper contains the results of an experimental investigation into the effect of a jet issuing from two afterbodies (one a right cylinder and the second conical) at incidence to a uniform subsonic flow. The tests were performed at a Reynolds Number of 0.3 x 10^6 based on body diameter and maximum turnel velocity. The presence of the jet issuing from an afterbody at incidence significantly increases the magnitude of the normal force, axial force and pitching moment arising from the external forces but not including the direct reaction of the jet. On the bluff cylindrical afterbody the effect of the jet is comparable in magnitude to the effect of incidence. However the effect of the jet on the conical afterbody is secondary to the effect of incidence.